Washington State Dental Society members, Alaska Yukon Pacific Exposition, Seattle, July 16, 1909. - Curtis, Asahel, 1874-1941 (1909)
On verso of image: Dentists On verso of image: Dentists To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number